The Relationship Between Physical And Mental Workload With Fatigue On Nurses - Indah Budi Lestari; Nusavia Astra Jingga; Y. Denny A. Wahyudiono (Universitas Airlangga, 2023)
Introduction: Workload and work fatigue are problems that often arise in a hospital. The unbalanced workload of nurses can cause work fatigue in the nurse workforce. If nurses experience work fatigue, the work motivation of the nurses will decrease, performance is low, work quality is low, there are many mistakes, low work productivity, work-related stress, occupational diseases, injuries, and work accidents. This study aims to analyze the relationship between physical workload and mental workload with work fatigue on nurses in the Emergency Room at Haji General Hospital Surabaya. Methods: This study was an observational study with a cross sectional study design. Conducted in the Emergency Room Installation of Haji General Hospital Surabaya with a research population of 30 nurses. The sampling technique was total sampling. The independent variable in this study is physical workload and mental workload while the dependent variable in this study is work fatigue. Data collection using direct measurement instruments in the form of a Pulse Oxy Meter, NASA-TLX and IRFC questionnaires with statistical analysis using the contingency coefficient test and the Spearman correlation test. Results: This study shows that physical workload has a very weak relationship with work fatigue on nurses (correlation coefficient 0.198) while mental workload has a strong enough relationship with work fatigue in acne (correlation coefficient 0.535). Conclusion: it can be concluded that physical workload and mental workload have a relationship with work fatigue on nurses in the Emergency Department of the Haji General Hospital of Surabaya. Keywords: Fatigue, mental workload, physical workload